Hazard Identification, Risk Assessment and Risk Control of Waterbase Tank Cleaning Operations - HARRIS HAKIMY YUSRIMAN; Mohd Dzulkifli, Syahrun Neizam (Progress in Engineering Application and Technology, 2026)
In many manufacturing companies, workplace accidents, occupational diseases, and injuries remain major concerns that can affect employee wellbeing, productivity, and overall operational efficiency. These issues are often associated with weaknesses in hazard identification and risk assessment practices, especially when work involves non-routine or high-risk operations such as tank cleaning. Tank cleaning is particularly challenging because it may involve confined space entry, exposure to chemical residues, poor ventilation, slippery surfaces, and the potential for equipment-related hazards if isolation procedures are not properly applied. Therefore, the purpose of this research is to evaluate the hazards and potential dangers during tank cleaning operations in an adhesive manufacturing company using a qualitative approach. This study applies Hazard Identification, Risk Assessment and Risk Control (HIRARC) as the main framework, supported by systematic field observations and a comprehensive review of relevant literature to strengthen the assessment. By combining these methods, the study aims to identify key hazards, determine the level of risk associated with each activity, and recommend suitable control measures based on the hierarchy of controls. The outcomes of this research will support risk reduction efforts and promote safer and healthier working conditions for tank cleaning operations.